If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 13x + 16 Reorder the terms: -2 + 4x = 13x + 16 Reorder the terms: -2 + 4x = 16 + 13x Solving -2 + 4x = 16 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -2 + 4x + -13x = 16 + 13x + -13x Combine like terms: 4x + -13x = -9x -2 + -9x = 16 + 13x + -13x Combine like terms: 13x + -13x = 0 -2 + -9x = 16 + 0 -2 + -9x = 16 Add '2' to each side of the equation. -2 + 2 + -9x = 16 + 2 Combine like terms: -2 + 2 = 0 0 + -9x = 16 + 2 -9x = 16 + 2 Combine like terms: 16 + 2 = 18 -9x = 18 Divide each side by '-9'. x = -2 Simplifying x = -2
| 2(15r+10)=-80 | | 17f+8=18f-6 | | 7w-w=6w | | (14x)Y-7=(7x)Y+7 | | 10b-8=10b+7 | | 2(x+3)x=5 | | -1xy=10+2y | | -7-4f=-4f-1 | | 100+y=23 | | 5y+4y-12=0 | | y=-0.3x^2+2.4x+4 | | x^2y-16y^3=0 | | x+-7=10 | | v=35v-16 | | 0=r-r | | 12x+12=11x-44 | | -12(x-0.5)+3=-6x+75 | | 6(4+5)=2f-8 | | 10h=-1+10h | | z=15+2(x+y)findx | | 17x^3+34x^2-85x-102=0 | | -6+8v=5v | | f(x)=7Ln(3x+2) | | -6+8=5v | | 3x+9+18x+3=264 | | t*2=2 | | youre=dung | | q=10q-9q | | 3x+9+18x+3=150 | | 7z+12=6z+11 | | 7.33-14.6x=7.98x+1.28 | | 10r+20=15r |